ANALISIS TEOLOGIS TANGGUNG JAWAB ORANG TUA KRISTEN DALAM PENDAMPINGAN PEMBELAJARAN DARING TERHADAP PENGARUH GADGET BAGI PERKEMBANGAN KOGNITIF ANAK USIA 7-11 TAHUN - Jonidius Illu; Dyulius Thomas Bilo; Yublina Kasse (Phronesis: Jurnal Teologi dan Misi, 2021)
Cognitive development is influenced by the environment including gadgets so that if children use gadgets excessively it can affect cognitive development. That is why the use of gadgets during online learning if used properly and effectively then gadgets is useful in improving children's cognitive and vice versa, if gadgets are used during online learning with a purpose that is not in the portion of online learning it will interfere with cognitive development which can have an impact on children's lives. One of the problems that have an impact on children's cognitive is the online learning factor. Because many children do not use time effectively during online learning. Cognitive development has been influenced by gadgets. This problem is caused by online games that appear during online learning, unattractive presentation of material from a teacher, boredom of children during online learning and the amount of ineffective time during online learning as a result, children spend a lot of time playing gadgets. For almost two years (2019-2021), there are parents who have difficulty controlling the gadgets used by their children, so through this article it is hoped that they can find out whether the influence of gadgets on online learning on the cognitive development of children aged 7-11 years, both positive and negative impacts negative The method in this writing is qualitative, meaning that by using library research, namely collecting data from various sources to obtain information in order to find appropriate information to be usedThe purpose of this paper is to obtain information related to the influence of gadgets on online learning on the cognitive development of children aged 7-11 yearsSo it can be concluded that this research is necessary because of the wrong use of gadgets during online learning. This is where the role of parents in providing assistance so that children use good gadgets so as not to have a bad impact on children's cognitive development.